Isolation and Identification of Black Oil-Degrading Bacteria From Lubricant-Contaminated Soil in Northern Baghdad, Iraq - Zeena Ghazi Faisal; Mohannad Mohammed Jameel; Othman Abbas Abdullah (The Scientific World Journal)
Black oil is a refined petroleum product that poses a significant environmental risk. It contains complex multihydrocarbons that decompose slowly, so black oil remains in the environment for a long time, causing various toxic effects. This study isolates and identifies an indigenous bacterium from soil samples contaminated with waste lubricating oil and evaluates its potential for degrading black crude oil. Twelve species of black oil-degrading bacteria were isolated from six soil samples of automobile and motorcycle workshops in the Al-Tarmiyah District of Baghdad, Iraq. Isolated bacteria were identified based on morphological and VITEK 2 system as Pseudomonas aeruginosa, Bacillus cereus, Burkholderia cepacia, Pseudomonas fluorescens, Acinetobacter lwoffii, Acinetobacter radioresistens, Stenotrophomonas maltophilia, and Streptococcus parasanguinis. Among these, based on the measurement of optical density and chromatogram analysis, B. cereus exhibited the maximum efficiency in degrading black oil, followed by P. aeruginosa. Therefore, these indigenous bacteria have the potential to be used in black oil removal from contaminated sites and the expansion of bioremediation approaches.